Allo-SCT using BU, CY and melphalan for children with AML in second CR - Beier, Rita; Albert, M. H.; Bader, Peter; Borkhardt, Arndt; Creutzig, U.; Eyrich, Max; Ehlert, K.; Gruhn, Bernd; Greil, Johann; Handgretinger, Rupert; Holter, W.; Klingebiel, Thomas; et al. (Bone marrow transplantation, 2013)
children, AML, BU, CY, melphalan, CR2
Gesehen am 19.01.2021
First published: 29 October 2012